Long-chain and very long-chain ceramide levels in subjects with impaired glucose regulation - Dimova, Rumyana; Lozanova, Vesela; Chakarova, Nevena; Serdarova, Mina; Kirilov, Georgi; Lozanov, Valentin; Del Prato, Stefano; Tankova, Tsvetalina (Journal of clinical lipidology, 2025)
•Ceramide levels and ratios seems to be similar in subjects with 1hr-OGTT and IGT.•C16:C24 and C18:C24 ratios appear to be lower in insulin resistance.•C16:0 ceramide is independently related to stimulated insulinemia, highlighting the leading role of some specific ceramide subspecies rather than total ceramide levels in the development of insulin resistance and beta-cell dysfunction.•The present study confirms the independent relationship between C16 and C18 ceramides and kidney function in early stages of glucose intolerance. The aim of this study was to determine the ceramide subspecies profile in people with impaired 1-hr or 2-hr postload glucose during a 75g oral glucose tolerance test (OGTT) and their association with cardio-metabolic parameters. Out of 90 subjects (age 46.7±10.5 years; BMI of 32.0±6.3 kg/m2) who underwent a 2-hr OGTT 19 had normal glucose tolerance (NGT), 22 1-hr plasma glucose ≥8.6 mmol/l (1hrOGTT), and 49 2-hr >8.6 and ≤10 mmol/l (IGT). HOMA-IR was determined and each group was subdivided into 2 subgroups (HOMA-IR<2.5 or ≥2.5). AUC for glucose, insulin, C-peptide and triglycerides were calculated during the OGTT. Ceramides were assessed by LC-MS on a fasting blood sample. There was no significant difference across the glucose tolerance groups as well the subgroups depending on HOMA-IR index for all evaluated lipid markers and ratios. The AUCC-peptide was positively associated with C16 (r=0.21, p=0.051), while a negative relationship was apparent between ISSI-2 and C24 (r=-0.21, p=0.051), HOMA≥2.5 and the C16/24 (r=-0.22, p=0.034), C18/24 (r=-0.22, p=0.037), and C24:1/C24 (r=-0.24, p=0.022) ratios. Multiple regression analysis showed an independent relationship between eGFR and C16 and C18 levels as well as between AUCC-peptide and C16. Our results demonstrate diminished C16:C24 and C18:C24 ratios in subjects with insulin resistance, and independent relationship between C16:0 ceramide and stimulated insulinemia, and between C16 and C18 and kidney function, highlighting the leading role of specific ceramide subspecies rather than the overall ceramide levels for the cardiometabolic profile in early stages of glucose intolerance.